A contribution for the identification of the azo reductase activity in intact yeast cells - Ramalho, Patrícia A. (2004)
Poster apresentado no International Congress on Yeasts (ICY) -Yeasts in Science and Biotechnology : The Quest for Sustainable Development", 11, Rio de Janeiro, Brasil, Agosto 2004.